EVALUASI PROGRAM BIMBINGAN DAN KONSELING DI MTS NEGERI 1 MEDAN - Amal Hayati; Ajeng Wulan Fitriani; Nabiilah Husnaa Br. Tarigan; Nuraisah Rizki Syahputri (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
Evaluation of guidance and counseling is an effort to determine the level of quality of the implementation of the guidance and counseling activity program. evaluation is very important for BK's development program. If the evaluation of the counseling guidance program is not carried out, the bk teacher will not know the success of the implementation of the guidance and counseling he has provided. Therefore, this study aims to determine the implementation of the evaluation of the guidance program at MTs Negeri 1 Medan. This study used quantitative research methods of descriptive statistical analysis techniques with a population of 330 students in grades 71-711 and a sample of 29 students from grades 78 and 2 teachers BK  from MTs Negeri 1 Medan. The results revealed that the implementation of the evaluation of the guidance and counseling program is included in the high category, meaning that teachers BK  carry out the evaluation process well as evidenced by several aspects that are visible, including personnel evaluation, program evaluation, and result evaluation. This is supported by guidance and counseling programs provided to students according to the analysis of student needs